Sb alloying for engineering high-thermoelectric zT of CuGaTe2 - Zhang, Danwei (2024)
Decades of studies on thermoelectric materials have enabled the design of high-performance materials based on basic materials properties, such as bandgap engineering. In general, bandgap energies correspond to the temperature at which the peak thermoelectric performance occurs. For instance, CuGaTe2 with a relatively wide bandgap of 1.2 eV has its peak zT > 1 at > 900 K. On the other hand, the zT is usually very low (<0.1) for this material at room temperature. This severely limits its average zT and hence overall performance. In this study, a phase diagram-guided Sb alloying strategy to improve the low-temperature zT of CuGaTe2 is used, by leveraging on the solubility limits to control the formation of the microstructural defects. The addition of Sb simultaneously improves the electrical conductivity and decreases the lattice thermal conductivity. For a low-temperature range of 300–623 K, this Sb-alloying strategy enables the achievement of a record high average zT of 0.33. The strategy developed in this study targets the improvement of the low-temperature range of CuGaTe2, which is rarely focused on for wide-bandgap ABX2 compounds, opening up more opportunities for holistic performance improvements, potentially enabling ultrahigh-performance thermoelectrics over a wide temperature range.